Preeclampsia among women with COVID-19 during pregnancy and its impact on maternal and perinatal outcomes: Results from a national multicenter study on COVID in Brazil, the REBRACO initiative - Guida, José P.; Cecatti, Jose G.; Souza, Renato T.; Pacagnella, Rodolfo C.; Ribeiro-do-Valle, Carolina C.; Luz, Adriana G.; Lajos, Giuliane J.; Surita, Fernanda G.; Nobrega, Guilherme M.; Griggio, Thayna B.; Charles, Charles M.; Miele, Maria J.; et al. (Elsevier, 2022)
Objective: To evaluate the prevalence of preeclampsia among cases of COVID-19 infection during pregnancy and the association between both conditions, in a multicenter cohort of Brazilian women with respiratory symptoms. Study design: Ancillary analysis of the Brazilian Network of COVID-19 in Obstetrics (REBRACO) study. We performed a nested case-control analysis selecting all women with COVID-19 and compared outcomes between women with and without PE. Main outcomes: Maternal, gestational, and clinical characteristics and perinatal outcomes. Measures: Prevalence ratio (PR) and its 95%CI for each of the predictors and outcomes. Results: A total of 203 women were included: 21 (10.3%) in PE group and 182 (89.7%) in non-PE group. Preeclampsia was not different among women with and without COVID-19 (10.3% vs 13.1%, p-value = 0.41), neither complication such as eclampsia and HELLP syndrome. Chronic hypertension (33.4%) (p < 0.01) and obesity (60.0%) (p = 0.03) were the most frequent comorbidities in PE group, and they were significantly more frequent in this group. Women with PE had more cesarean section (RR 5.54 [1.33 – 23.14]) and their neonates were more frequently admitted to neonatal intensive care unit (PR 2.46[1.06 – 5.69]), most likely due to preterm-birth-related complications. Conclusion: The prevalence of PE among women with COVID-19 infection during pregnancy was around 10%; women with COVID-19 and a history of chronic hypertension or obesity are more likely to have preeclampsia. Cesarean section is increased among women with PE and COVID-19, with increased rates of neonatal admission to intensive care units, mostly due to prematurity.
Keywords: COVID-19; Maternal health; Pandemic; Preeclampsia; Pregnancy complications